172k views
4 votes
3 + 4 X 3-3 X 5
What is the answer

User Rob Moll
by
5.2k points

1 Answer

6 votes

Remember the Rules of Operations (PEDMAS):

Parentheses

Exponents

Multiplication

Division

Addition

Subtraction

So with the expression 3 + 4 x 3 - 3 x 5 we know to multiply first. So let's multiply 4 x 3 and -3 x 5 first:

3 + 4 x 3 - 3 x 5

= 3 + 12 - 15

Then let's work out the rest of the expression!

3 + 12 - 15

= 15 - 15

= 0

Therefore we can determine that 3 + 4 x 3 - 3 x 5 = 0

I hope this helped! :)

User Jeromy French
by
4.4k points